Current Situation and Optimization Strategies of Student Status Management in Universities - Wei Tiansheng; Sun Yan; Mi Congcong (Pacific International Journal, 2024)
Student status management is an important part of higher education institutions’ work, which is crucial for maintaining teaching order, safeguarding students’ rights and improving educational quality. In recent years, with the expansion of higher education enrollment scale and the development of information technology, higher education institutions have faced new opportunities and challenges in student status management. This article discusses the problems that exist in SSM, including the deficiencies in institutional construction, informationization construction, data confidentiality, personnel professional qualifications, and service improvement, and proposes strategies for solving these problems. The proposed optimization strategies cover improving the management system and process, enhancing team qualities, promoting information.